Pembangunan Berkelanjutan (SDGs): Sociopreneur Zakat Produktif Sebagai Upaya Pengentasan Kemiskinan - Nabilla Amirah; Hamda Sulfinadia; Efirnaldi Efrinaldi (Al-Intaj)
The purpose of this research is to analyze the business activities of the productive zakat distribution that have been carried out by Dompet Dhuafa Singgalang and to analyze the role of the productive zakat sociopreneur program in efforts to realize sustainable development (SDGs). This research is field research with a qualitative descriptive approach. The data sources used a primary data sources and secondary data sources and data collection techniques are interview. Based on the results of the analysis carried out, it is clear that productive zakat actively participates in sociopreneur activities by financing eight goals of zakat recipients with the concept of social entrepreneurship including the Kampuang Nila Program in Pauh Padang City, Solok Sirukam Coffee Village Program, DD Farm Padang Pariaman Center, DD Farm Solok Sirukam Center, Minang Sepakat Souvenir Center and Kampoeng Ternak in Ampuan Lumpo Pesisir Selatan. The role of the productive zakat sociopreneur program in efforts to realize sustainable development (SDGs) has a very good impact so that this has a positive impact on the community..